HETEROGENITY AND ROCK TYPE (RT) ANALYSIS CARBONATE RESERVOIR BATURAJA FORMATION, OKU FIELD, SOUTH SUMATRA BASIN - Kusumaningtyas, Indah
OKU Field is an oil fields that located in South Palembang Sub-Basin. This field produces oil from carbonate reservoir in Baturaja Formation. Generally, carbonate reservoir has a non linear relationship between porosity and permeability, depending on the way it was deposited and the process afterward. Therefore analysis of carbonate reservoir heterogeneity in Baturaja Formation is important to do. It is to support the development of that field. The method for understanding and mapping of reservoir characteristic and heterogeneity is integrating rock type, depositional facies, and diagenesis analysis. Rock type analysis is used to understand and classify rock property whilst depositional facies analysis is used to map the rock based on the depositional environment and diagenesis analysis is used to understand the processes that occur after the rock was depositioned which control the quality of rock property. The scopes of this research are lithofacies analysis, depositional facies analysis, diagenesis analysis, rock type classification analysis, and relationship analysis between rock type, facies, and diagenesis in Baturaja Formation, OKU Field. The available data for this research are 40 wells of wireline logs, two wells of core analysis reports, and a side wall core analysis report. Based on the lithofacies analysis, it can be known that limestone of Baturaja Formation in OKU Field can be classified into eight lithofacies, they are Coral Wackestone, Moluska Wackestone, Foram Wackestone, Echinoderm Packstone, Bentonite Foram Wackestone, Red Algae Packstone, Indeterminate bioclast Packstone, dan Mudstone. Based on the results of depositional facies analysis, it is known that carbonate rocks in the Baturaja Formation at OKU Field are associated with interior platforms (open marine interior platforms to restricted), reef margin platforms, reef and slope. The diagenesis process which control the reservoir quality in this field are micritation, dissolution, neomorphism, and burial. The results of thin section review in this reservoir show several diagenesis zones, such as: marine phreatic, meteoric vadose, meteoric phreatic and burial zones. Rock property analysis was iniatied by identify of flow unit which called rock type analysis. Rock type was created with two approaches, RQI (reservoir quality index) and FZI (flow zone indicator). In this method, every rock type shows the relationship between porosity and permeability that was reflected in correlation coefficient number. Based on FZI method, limestone in Baturaja Formation can be grouped into five rock type, they are RT-1 (vuggy 50%-fracture 50% porosity), RT- 2 (vuggy 40%-intragranular 20%-micropore 40% porosity), RT-3 (vuggy 73%- fracture 18%-micropore 9% porosity), RT-4 (vuggy 67%-fracture 2%-micropore 31% porosity), dan RT-5 (micropore 40%-vuggy 60% porosity). Based on the relation between rock type and porosity type, it can be known that the limestone quality on every rock type is affected by type of porosity and the percentage of porosity type appearance.